2017
DOI: 10.19080/ctbeb.2017.04.555644
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Ag, Co, Cr, Fe, Hg, Rb, Sb,Sc, Se, and Zn Contents in Intact Thyroid of Males Investigated by Neutron Activation Analysis

Abstract: A prevalence of thyroid dysfunction is higher in the elderly as compared to the younger population. An excess or deficiency of trace element contents in thyroid plays important role ingoitro-and carcinogenesis of gland. The variation with age of the mass fraction of ten trace elements (Ag, Co, Cr, Fe, Hg, Rb, Sb, Sc, Se, and Zn) in intact (normal) thyroid of 62 males (mean age 35.9 years, range 2-80) was investigated by instrumental neutron activation analysis with high resolution spectrometry of long-lived ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 31 publications
(35 reference statements)
6
43
0
Order By: Relevance
“…The ratios of means and the difference between mean values of Br, Ca, Cl, I, K, Mg, Mn, and Na mass fractions in normal thyroid of females and males are presented in Table 4. Because, in our previous studies age-dependents of many ChE in thyroid gland was found [51][52][53][54], the comparison between ChE contents in thyroid of females and males separately in age group 1 and in age group 2 was also performed (Tables 5 & 6). The data of inter-correlation calculations (values of r -coefficient of correlation) including all ChE identified by us in thyroid of females and males separately are presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…The ratios of means and the difference between mean values of Br, Ca, Cl, I, K, Mg, Mn, and Na mass fractions in normal thyroid of females and males are presented in Table 4. Because, in our previous studies age-dependents of many ChE in thyroid gland was found [51][52][53][54], the comparison between ChE contents in thyroid of females and males separately in age group 1 and in age group 2 was also performed (Tables 5 & 6). The data of inter-correlation calculations (values of r -coefficient of correlation) including all ChE identified by us in thyroid of females and males separately are presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study a significant positive correlation between age and some trace element contents in the thyroid was observed [23][24][25][26][27][28]. For example, a strongly pronounced tendency of age-related increase in bromine (Br), coper (Cu), rubidium (Rb) and zinc (Zn) mass fraction was demonstrated by us using 109 Cd radionuclide-induced energy dispersive X-ray fluorescent (EDXRF) analysis [26,28].…”
Section: Introductionmentioning
confidence: 87%
“…A vertical channel of the WWR-c research nuclear reactor (Branch of Karpov Institute, Obninsk).was applied to determine the content of Ag, Co, Cr, Fe, Hg, Rb, Sb, Sc, Se, and Zn by INAA-LLR. Details of used neutron flux, nuclear reactions, radionuclides, gamma-energies, and spectrometric unit were presented in our earlier publications concerning the INAA-LLR of ChE contents in human thyroid, scalp hair, and prostate [29,30,51,54].…”
Section: Sample Preparation and Methodsmentioning
confidence: 99%
“…Level of I in the normal thyroid was investigated in relation to age, gender and some non-thyroidal diseases [23,24]. After that, variations of ChE content with age in the thyroid of males and females were studied and age-and gender-dependence of some ChE was observed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Furthermore, a significant difference between some ChE contents in normal and cancerous thyroid was demonstrated [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%